Social aspects of running events participation in rural areas – the impact on health and physical activity - Poczta, Joanna; Malchrowicz-Mośko, Ewa (Journal of Education, Health and Sport, 2018)
Abstract Introduction: The main purpose of the research is to determine the impact of the organization of running events in rural areas on promoting health and undertaking physical activity. Material and methods: In order to elicit the opinions of the participants of the marathon on the popularization of running, health and physical activity, a diagnostic survey was carried out during "Run of the Lion", where 312 participants of the race (both passive and active) were examined. Results: Examined participants of the race, where as much as 86% of the 312 respondents believe that the marathon and all the attractions associated with the event have an impact on the popularization of healthy lifestyles, both among the residents and passive spectators. Conclusions: The trends observed in the Polish society lead to the reflection about the motives that guide people involved in running the marathon. In the context of everyday life both trainings and running marathons itself require a lot of free time. Sports events in the modern world play the role of promoting health and physical activity also among the fans.